THE EFFECT OF COMPANY SIZE, INVESTMENT RETURNS, AND PROFITABILITY ON THE SOLVENCY OF SHARIA INSURANCE IN INDONESIA FROM 2012 TO 2016 - Ambarwati, Samiari; Hasib, Fatin Fadhilah (Universitas Airlangga, 2018)
The purpose of this study is to determine the effect of partial and simultaneous Company Size, Investment Return, and Profitability on Solvency with proxy of RBC at Sharia Insurance in Indonesia period 2012-2016. This study uses a quantitative approach. Sampling technique is purposive sampling and there were 17 sharia general insurance and sharia life insurance company in Indonesia as subject of research. Analysis technique used is panel data regression by using Fixed Effect Model (FEM). The results of this study indicate that simultaneously company size, investment return, and profitability significantly influence the solvency of Takaful insurance in Indonesia. And partially variable of company size have positive and significant influence, variable investment return has no significant effect, and variable of profitability has no significant effect to solvency of sharia life insurance in Indonesia period 2012-2016.Keywords: Company Size, Invesment Return, Profitability, Solvency, Islamic Insurance